An investigation of media reports of digital surveillance within the first year of the COVID-19 pandemic - Leigha Comer; Lorie Donelle; Lorie Donelle; Marionette Ngole; Jacob J. Shelley; Anita Kothari; Maxwell Smith; James M. Shelley; Saverio Stranges; Saverio Stranges; Saverio Stranges; Saverio Stranges; et al. (Frontiers Media S.A., 2023)
IntroductionThe COVID-19 pandemic prompted a surge in digital public health surveillance worldwide, with limited opportunities to consider the effectiveness or impact of digital surveillance. The news media shape public understanding of topics of importance, contributing to our perception of priority issues. This study investigated news media reports published during the first year of the pandemic to understand how the use and consequences of digital surveillance technologies were reported on.MethodsA media content analysis of 34 high- to low-income countries was completed. The terms "COVID-19," "surveillance," "technologies," and "public health" were used to retrieve and inductively code media reports.ResultsOf the 1,001 reports, most were web-based or newspaper sources on the development and deployment of technologies directed at contact tracing, enforcing quarantine, predicting disease spread, and allocating resources. Technology types included mobile apps, wearable devices, "smart" thermometers, GPS/Bluetooth, facial recognition, and security cameras. Repurposed data from social media, travel cards/passports, and consumer purchases also provided surveillance insight. Media reports focused on factors impacting surveillance success (public participation and data validity) and the emerging consequences of digital surveillance on human rights, function creep, data security, and trust.DiscussionDiverse digital technologies were developed and used for public health surveillance during the first year of the COVID-19 pandemic. The use of these technologies and witnessed or anticipated consequences were reported by a variety of media sources worldwide. The news media are an important public health information resource, as media outlets contribute to directing public understanding and shaping priority public health surveillance issues. Our findings raise important questions around how journalists decide which aspects of public health crises to report on and how these issues are discussed.